Materialism and big-five personality traits shaping low-income university students' compulsive online-buying behavior - Burhan, Nik Ahmad Sufian; Keshminder, J. S.; Sabri, Mohamad Fazli; Salleh, Fauzilah; Afthanorhan, Asyraf; Joey, Chan (Universiti Putra Malaysia, 2022)
Despite the immense benefits of online shopping in modern societies, it has also generated some concern about addiction among consumers, particularly the unemployed youth from low-income families. Thus, by conducting a path analysis on quantitative survey data of randomly sampled 439 respondents, this study examines the influence of materialistic behavior and the Big-Five personality traits on the compulsive online-buying behavior of university students from low-income families (the B40 income group). Among the five personality traits, an increase in neuroticism scores, openness to experiences, and conscientiousness was observed to raise the level of materialism significantly. Similarly, materialism, neuroticism, and extraversion exhibited a direct positive influence on the compulsive online-buying behavior of the students. These findings reiterate that individuals with higher neuroticism tend to display less self-regulation or emotion control. In contrast, more extroverted individuals tend to be engrossed with the interactive on-screen platform, which cultivates their obsession with online shopping. Importantly, the mediation test showed that materialistic behavior significantly mediates the effects of neuroticism, openness to experience, and conscientiousness on compulsive buying. Overall, our findings projected neuroticism as dominating due to its direct and indirect influence on compulsive online-buying behavior in the path model.